Influence of Different Sizes of Brooding Box Made of Clay and Bamboo Basket on the Hatchability of Chicken Eggs Through Broody Hen - Islam, MS; Sarkar, MM; Uddin, MJ; Howlider, AR (Progressive Agriculture, 2014)
An experiment was conducted to hatch chicken eggs in two different types of brooding boxes made of clay and bamboo basket by using broody hen. Three different size boxes were used under each type which were large(48 × 33 × 18 cm), medium (43 × 28 × 18 cm) and small (38 × 23 × 18 cm) (i.e. diameter of upper portion × diameter of lower portion × height of brooding boxes). The objective was to identify the optimum size of the brooding box used for natural hatching and to identify the appropriate material for brooding box used for incubation of eggs under rural condition. The fertility was not significantly affected by the type and size of boxes. Hatchability, Chicks not pipped and dead in germ were not significantly affected by types of boxes made of clay and bamboo basket but significantly affected by the size of boxes (p<0.05). The dead in shell was significantly affected by types and sizes of brooding box made of clay and bamboo basket (p<0.05). The percentage of dead in shell increased with the decreasing size of brooding box. Finally, it was concluded that hatchability of Deshi chicken eggs incubated by broody hen can be affected by both materials and size of brooding box. The study has shown that hatchability increased with increased size of the box up to a certain level. On the other hand, clay box gives more hatchability than bamboo basket. DOI: http://dx.doi.org/10.3329/pa.v18i2.18168 Progress. Agric. 18(2): 123 - 133, 2007